Managing supply chain uncertainty arising from geopolitical disruptions: evidence from the pharmaceutical industry and brexit - Roscoe, Samuel; Skipworth, Heather; Aktas, Emel; Habib, Farooq (Emerald, 2020)
Purpose This paper examines how firms of different sizes formulate and implement strategies to achieve fit with an external environment disrupted by a geopolitical event. The context of the study is the pharmaceutical industry and how it managed the supply chain uncertainty created by the United Kingdom's decision to leave the European Union, or Brexit. Design/methodology/approach Data were collected longitudinally from the pro-Brexit vote on 23 June 2016, until the UK’s departure from the EU on 31 January 2020. Twenty-seven interviews were conducted in the pharmaceutical sector, including nineteen interviews with senior managers at eight case companies and eight interviews with experts working for trade associations and standards institutes. The interview findings were triangulated with Brexit policy and strategy documentation. Findings When formulating strategy, multi-national enterprises (MNEs) used worst case assumptions, while large firms, and small and medium sized enterprises (SMEs) gathered knowledge as part of a “wait-and-see” strategy, allowing them to reduce perceptions of heightened supply chain uncertainty. Firms then implemented reactive and/or proactive strategies to mitigate supply chain risks. Originality/value The study elaborates on strategic contingency theory by identifying two important conditions for achieving strategic fit: first, companies deploy intangible resources, such as management time, to gather information and reduce perceptions of heightened supply chain uncertainty. Second, companies deploy tangible resources (supply chain redundancies, new supply chain assets) to lessen the negative outcomes of supply chain risks. Managers are provided with an empirical framework for mitigating supply chain uncertainty and risk originating from geopolitical disruptions.
Keywords: supply chain risk management; supply chain uncertainty; contingency theory; Geopolitical risks